2017
DOI: 10.1002/ajmg.a.38329
|View full text |Cite
|
Sign up to set email alerts
|

Two patients with the heterozygous R189H mutation in ACTA2 and Complex congenital heart defects expands the cardiac phenotype of multisystemic smooth muscle dysfunction syndrome

Abstract: The authors have brought to our attention an error in their article title. R189H should be replaced with R179H. The corrected article title follows, "Two patients with the heterozygous R179H mutation in ACTA2 and Complex congenital heart defects expands the cardiac phenotype of multisystemic smooth muscle dysfunction syndrome". The authors and publisher regret this error.2566 |

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Another clinical study revealed that serum IFNG levels were significantly positively correlated with TG concentration in CHD patients, which could be involved in the development of atherosclerosis of the coronary artery [ 89 ]. ACTA2, the human aortic smooth muscle actin (SMA) gene typically expressed in VSMCs, contributes to vascular motility and contraction and may cause a variety of vascular diseases in the event of mutation, such as coronary artery disease and multisystemic smooth muscle dysfunction syndrome [ 90 , 91 ]. In experimental homozygous α-SMA knockout mice, decreased vascular contractility and reduced basal blood pressure were notable, suggesting the important role of α-SMA in maintaining vascular tone [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another clinical study revealed that serum IFNG levels were significantly positively correlated with TG concentration in CHD patients, which could be involved in the development of atherosclerosis of the coronary artery [ 89 ]. ACTA2, the human aortic smooth muscle actin (SMA) gene typically expressed in VSMCs, contributes to vascular motility and contraction and may cause a variety of vascular diseases in the event of mutation, such as coronary artery disease and multisystemic smooth muscle dysfunction syndrome [ 90 , 91 ]. In experimental homozygous α-SMA knockout mice, decreased vascular contractility and reduced basal blood pressure were notable, suggesting the important role of α-SMA in maintaining vascular tone [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…ACTA2 mutation has been recently identified as a major cause of familial thoracic aortic aneurysm and ductus arteriosus aneurysm. 7 Several MYH11 mutations have been implicated in adults with thoracic aortic aneurysms and patent ductus arteriosus. 8 A dominant causal variant in MYH11 associated with smooth muscle dysfunction has been reported recently in families with chronic intestinal pseudoobstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of congenital ductal aneurysm remains ill defined, although several theories have been postulated. 7 These include (a) delayed closure of the aortic end of the ductus, resulting in exposure of the ductal wall to systemic arterial pressure, (b) necrosis and mucoid degeneration of the media of the ductus, resulting in weakness of the wall, (c) congenital weakening of the ductal wall from defective elastin, resulting in abnormal intimal cushion formation, and (d) intrauterine constriction of the ductus close to the pulmonary end with post-stenotic dilation. In our patient, the likely mechanism of aneurysmal ductus is the failure to constrict after birth from defective smooth muscle myosin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tables 1-4 summarizes the systemic features of the reported patients with MSMDS worldwide[8-16]. SMCs are widely distributed in the gastrointestinal tract, urinary tract, respiratory tract, uterus, iris, and other body parts.…”
Section: Discussionmentioning
confidence: 99%